Health Education for Elementary School Age Children in the Kenosis Community, Surabaya - Juliana Christyaningsih; Yuni Ginarsih; Kasiati; Mujayanto; Nuning Marina Pengge; Kiaonarni O.W; Pratiwi Hermiyanti; Rahayu Sumaningsih; Lembunai Tat Alberta; Evi Yunita Nugrahini; Yohanes Kambaru W; Teta puji Rahayu; Nurwening TW; Hery Sumasto; Suliati; Lully Hani Endarini; Evy Diah Woelansari; Ira Puspita Sari; Ira Rahayu Tiyar; P, Teresia Retna; Museyaroh (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
ABSTRACT The tutoring center